EGFR/c-Met and mTOR signaling are predictors of survival in non-small cell lung cancer. (September 2020) - Crees, Zachary D; Shearrow, Caleb; Lin, Leo; Girard, Jennifer; Arasi, Kavin; Bhoraskar, Aayush; Berei, Joseph; Eckburg, Adam; Anderson, Austin D.; Garcia, Christian; Munger, Ariana; Palani, Sunil; et al.
Background: EGFR/c-Met activation/amplification and co-expression, mTOR upregulation/activation, and Akt/Wnt signaling upregulation have been individually associated with more aggressive disease and characterized as potential prognostic markers for lung cancer patients. Methods: Tumors obtained from 109 participants with stage I–IV non-small cell lung cancer (NSCLC) were studied for EGFR/c-Met co-localization as well as for total and active forms of EGFR, c-Met, mTOR, S6K, beta-catenin, and Axin2. Slides were graded by two independent blinded pathologists using a validated scoring system. Protein expression profile correlations were assessed using Pearson correlation and Spearman's rho. Prognosis was assessed using Kaplan–Meier analysis. Results: Protein expression profile analysis revealed significant correlations between EGFR/p-EGFR ( p  = 0.0412) and p-mTOR/S6K ( p  = 0.0044). Co-localization of p-EGFR/p-c-Met was associated with increased p-mTOR ( p  = 0.0006), S6K ( p  = 0.0018), and p-S6K ( p  < 0.0001) expression. In contrast, active beta-catenin was not positively correlated with EGFR/c-Met nor any activated proteins. Axin2, a negative regulator of the Wnt pathway, was correlated with EGFR, p-EGFR, p-mTOR, p-S6K, EGFR/c-Met co-localization, and p-EGFR/p-c-Met co-localization (all p -values <0.03). Kaplan–Meier analysis revealed shorter median survival in participants with high expression of Axin2, total beta-catenin, total/p-S6K, total/p-mTOR, EGFR, and EGFR/c-Met co-localization compared with low expression. After controlling for stage of disease at diagnosis, subjects with late-stage disease demonstrated shorter median survival when exhibiting high co-expression of EGFR/c-Met (8.1 month versus 22.3 month, p  = 0.050), mTOR (6.7 month versus 22.3 month, p  = 0.002), and p-mTOR (8.1 month versus 25.4 month, p  = 0.004) compared with low levels. Conclusions: These findings suggest that increased EGFR/c-Met signaling is correlated with upregulated mTOR/S6K signaling, which may in turn be associated with shorter median survival in late-stage NSCLC.